THE CONSTRUCTION OF DIGITAL TABARRUJ IN Q.S. AL-AHZAB:33 IN RELATION TO THE PHENOMENON OF EXHIBITIONISM ON SOCIAL MEDIA - Syarafina Tsiqa Syafura S; Achmad Abubakar; Aisyah Arsyad; A. Muh Fakhrul Ahsan (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2026)
The phenomenon of digital exhibitionism, namely the excessive self-display behavior on social media platforms, has become an urgent ethical issue in the era of digital transformation, particularly in Indonesia, where the number of social media users reached 180 million in 2025. This study aims to analyze the relevance of the concept of tabarruj in Q.S. al-Ahzab:33 to the contemporary phenomenon of digital exhibitionism through a Qur’anic exegesis approach. This research employs a qualitative method by referring to relevant Qur’anic exegesis works and supported by primary sources from books and contemporary academic studies. The findings indicate that tabarruj, semantically rooted in the word b-r-j, which means “to appear prominently” or “to become visible,” has a strong conceptual resonance with digital exhibitionism practices, in which individuals intentionally display themselves to gain social validation. This study introduces the concept of “digital tabarruj” as a new conceptual construct that bridges classical Qur’anic interpretation with the ethical realities of modern digital life. The findings affirm that the prohibition of tabarruj in the Qur’an is universal and remains relevant across different periods, while recommending the integration of Qur’anic values into digital literacy education in Indonesia.